Rola zaburzeń w regeneracji lasu - Dobrowolska, Dorota (Leśne Prace Badawcze, 2010)
The definitions, history and characteristics of disturbances are presented. Natural disturbances are the key processes in forest ecosystems. The establishment of many of the world’s forests has been governed by natural disturbances. The list of natural disturbances is very long and varied. They can be split into biotic and abiotic groups: biotic disturbances are caused by insects and pathogens. The most important abiotic disturbances are forest fires, windthrough and floods. In Holling’s Model describing the development of ecosystems, natural and anthopogenic disturbances are divided into two groups according to their scale. The first group contains gaps that are created by the death of one or several trees in a forest. The other group consists of the large scale disturbances e.g. forest fires. Examples of gaps and large-scale disturbances in Polish forests are given in the paper. Natural disturbances should be considered as a permanent element of forest ecosystems.